183 A blend of plant extracts (Actifor Pro) potentially reduced methane production in a dual-flow continuous culture system fed bermudagrass hay with or without corn gluten feed. (30th November 2020) - Garcia-Ascolani, Mariana E; DiLorenzo, Nicolas; Sun, Yan; Aubert, Thierry; Larson, Haley
Abstract: Twelve dual-flow continuous culture fermenters (1.95 L) were used to evaluate the effect of a phytogenic feed additive (Actifor Pro, Delacon, Engerwitzdorf, Austria; ACT) on ruminal fermentation and methane production when fed high fiber diets, comprised of bermudagrass hay (BGH) with or without corn gluten feed (CGF). Fermenters were utilized in a generalized randomized block design with a 2 × 2 factorial arrangement of treatments (n = 6): 1) diet (with or without CGF at 22% of diet DM) and 2) additive (with or without ACT at 1.0 g/L ACT). Two 10-d periods were conducted. Overall, comparing to no CGF, supplementation with CGF resulted in lower dry matter, organic matter, crude protein digestibility, microbial efficiency of nitrogen utilization, and methane production (mL of CH4 /mol of total VFA), but increased neutral detergent fiber digestibility (all P ≤ 0.05). Diet × additive interactions were observed for molar proportion of acetate and propionate, and acetate-to-propionate ratio (A:P, all interactions P < 0.05), where inclusion of ACT increased acetate molar proportion and A:P (both P < 0.05), and decreased propionate molar proportion in diets with CGF (P = 0.05). A diet × additive interaction was also observed for methane production (ml of CH4 /mol of total VFA; P = 0.08), where ACT decreased CH4 production per mol of VFA by 42% (P = 0.04), when only BGH was fed to the fermenters. In conclusion, CGF supplementation in BGH diets reduced methane production and improved fiber digestibility. The decrease in methane production per mol of VFA observed with ACT in the BGH without CGF diet warrants further investigation.